ET-4 BASIC RESEARCH OF BORON NEUTRON CAPTURE THERAPY USING A NOVEL BORON COMPOUND TARGETED TO INTEGRIN. (3rd December 2022) - Tsujino, Kohei; Kawabata, Shinji; Kashiwagi, Hideki; Yoshimura, Kohei; Kayama, Ryo; Fukuo, Yusuke; Kanemitsu, Takuya; Hiramatsu, Ryo; Hu, Naonori; Miyatake, Shin-Ichi; Nishimura, Kai; Takata, Takushi; et al.
Abstract: Background: Boron neutron capture therapy (BNCT) is a particle radiation modality capable of selectively destroying tumor cells. The most commonly used boron compound for BNCT is boronphenylalanine (BPA). BPA is taken up into the tumor cell via the L-type aminoacid transporter (LAT-1). However, there are some BPA-refractory situations. Therefore, a novel boron compound is expected to improve the therapeutic performance of BNCT. We focused on integrinαvβ3, which is overexpressed in malignant gliomas as in many cancer cells, and have developed cRGD-MID-AC, a conjugate of cyclic RGD (cRGD), which selectively inhibited integrinαvβ3, and MID-AC, which we have already reported as effective on BNCT as BPA as a boron compound in F98 rat glioma models. We evaluated the efficacy of BNCT using this novel compound.Methods: F98 glioma cells were exposed to BPA, cRGD-MID-AC, and cRGD-MID for cellular uptake and neutron irradiation experiment. Intracellular boron concentrations and compound biological effectiveness (CBE) for each boron compound was calculated. After intravenous administration (i.v.) of cRGD-MID-AC or BPA, the biodistribution of boron compounds was measured and neutron irradiation experiment were performed in F98 rat glioma models. Results: Intracellular boron concentrations of BPA and cRGD-MID-AC were increased gradually at all exposed time, and CBE for cRGD-MID-AC was comparable to that for BPA. In cRGD-MID-AC, the boron concentration in the tumor was the highest at 8 h after i.v. and tended to be retained longer at 24h. In vivo neutron irradiation experiment, long-term survival was observed only in the group irradiated 8 h after cRGD-MID-AC i.v.. These experiments suggest that cRGD-MID-AC has sufficient cell-killing effect and may be more effective in vivo. Conclusion: cRGD-MID-AC has a tumor accumulation mechanism different from that of BPA, and could be an effective boron carrier in BNCT for malignant gliomas.